2022
DOI: 10.1186/s13049-022-01001-9
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of trauma patients in Sweden during the first months of the COVID-19 pandemic: a small reduction in trauma admissions

Abstract: Background Given that Swedish authorities have been widely viewed as having practiced an unusual approach to the COVID-19 pandemic and given that Sweden is notable for a low incidence of trauma, we wanted to learn how the pandemic may have affected the number of trauma admissions in Sweden. Methods We conducted a retrospective cohort study based on the Swedish trauma registry (Svenska Traumaregistret). The study period was March 1, 2020 to June 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…They concluded that it was caused by the less significant social restrictions enforced by the Australian government than in other countries [38]. Comparable results were presented by Bäckström et al in the study of trauma admissions in Sweden, recorded in the Swedish trauma registry [39]. They noticed a reduction of 22% in all severe injuries.…”
Section: Trauma Volumementioning
confidence: 86%
“…They concluded that it was caused by the less significant social restrictions enforced by the Australian government than in other countries [38]. Comparable results were presented by Bäckström et al in the study of trauma admissions in Sweden, recorded in the Swedish trauma registry [39]. They noticed a reduction of 22% in all severe injuries.…”
Section: Trauma Volumementioning
confidence: 86%
“…Several studies assessed stab injury incidences during the COVID-19 pandemic, and most found a rise in penetrating injuries during the first months of 2020 ( 4 9 ), but not all ( 26 , 27 ). Conversely, it was reported that during the first months of the COVID-19 pandemic, crime rates, including assault, decreased globally ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…While overall patient volumes declined in emergency departments (EDs) during the COVID-19 pandemic, incidences of stabbing trauma increased in both Europe (4,5) and the United States (6)(7)(8)(9). Although most stab injuries are not fatal, thoracoabdominal injuries often require surgery and are associated with postsurgical complications and hospital readmissions (10).…”
Section: Introductionmentioning
confidence: 99%
“…Global healthcare providers have faced a historical crisis and have accumulated experiences and lessons during the pandemic. As a major part of critical care, the impact of the pandemic on trauma care has been investigated [ 1 3 ]. Overall road traffic volume reduction with social restriction, including lockdown or stay-at-home order, were observed and consequently resulted in a reduced number of motor vehicle accidents, emergency trauma surgeries, and trauma admissions [ 1 4 ].…”
Section: Introductionmentioning
confidence: 99%